Receiving Line in the Kellogg-Voorhis Manor House the Evening of the President's Reception
Part of the receiving line in the Kellogg-Voorhis manor house the evening of the president's reception. Shown in the line are Mr. and Mrs. McPhee, Mr. and Mrs. Englund, Mr. and Mrs. McCorkle, Mr. and Mrs. Young, Mr. and Mrs. Kennedy and George Clucas.